Cost-utility analysis of R-CHOP vs CHOP in patients with non-hodgkin's lymphoma: a systematic review - Cadag, Camille Francesca T.
Background: Non-Hodgkin Lymphoma (NHL) ranks 11th in cancer incidence and mortality in the Philippines with the combination chemotherapy composed of Cyclophosphamide, Doxorubicin, Vincristine, and Prednisone (CHOP) being commonly used as treatment. However, the addition of Rituximab to CHOP (R-CHOP) has been shown to exhibit higher response rates and longer remissions, potentially improving quality of life. Currently, there is conflicting evidence on the cost-utility of CHOP versus R-CHOP.